The Structure Equation Model of Online Purchasing Intentions During COVID-19 Lock down in Songkhla Province - Kettapan, Komonmanee (Economics and Business Administration Journal Thaksin University, 2022)
The purpose of this research is to develop and examine a structural equation model of causal factors which have affected on online purchasing intentions during COVID-19 lockdown in Songkhla province. This research is quantitative. Questionnaire was a method of data collection tool. The researchers asked 383 online shoppers in Songkhla province to fill in the questionnaire. SPSS program was used to analyze basic statistics and LISREL program was used to analyze the structural equation model. The research result found that structural equation model of causal factors had effects on online purchasing intentions. This model has been developed in accordance with the empirical data, where chi-square =175.23, df = 138, CMIN/Df = 1.27, p-value = 0.06, GFI = 0.90, AGFI = 0.86, SRMR = 0.05, and RMSEA = 0.02. It is an equation model which passed the criteria requirements. The result of the developed structural equation model analysis showed that experience of purchasing online had positive direct influences on perceived usefulness and perceived ease of information technology use. Perceived ease of information technology use had both directly and indirectly positive influence on online purchasing intentions. While, perceived usefulness had positive direct impact on online purchase intentions during COVID-19 Lockdown in Songkhla province, at significant 0.01 level.